Un Répertoire chronologique de lettres de Voltaire : Non recueillies dans les éditions de sa correspondance générale - Delattre, Andre (Studies in the Romance languages and literatures, 2018)
This general chronology of Voltaire's letters by an eminent "Voltairiste" contains a chronological appendix, followed by a bibliography and an index.